Dénomination des couleurs artistiques et décoratives en polonais - Kopecka, Anetta; Janic, Katarzyna (Neophilologica, 2016)
The present paper deals with the denomination of colors in Polish, and investigates the ways colors are conceptualized in two types of practices, artistic and decorative. Contrary to the universal approach advocated by Berlin and Kay (1969) which focuses on basic colors terms and which has been largely followed by scholars in linguistics and cognitive science, the present study shows how colors are expressed by a variety of lexical structures revealing the diversity of semantic domains from which they are drawn. Following Dubois and Grinevald (1999, 2003) and Dubois (2006, 2008, inter alia), the study points out to different modes of conceptualizing colors in artistic and decorative domains in order to show that color denomination is closely associated with specific cultural practices.